"We are different people": A narrative analysis of carers' experiences with mental health crisis and support from crisis resolution teams. Issue 6 (1st November 2016) - Klevan, Trude; Davidson, Larry; Ruud, Torleif; Karlsson, Bengt
ABSTRACT: Crisis resolution teams (CRTs) deliver acute mental health care in the community. This care implies collaboration with carers. The article explores experiences of mental health crisis from the carer's perspective and what carers experience as helpful and/or unhelpful help from CRTs. In-depth interviews with carers are analyzed using a narrative approach. The configuration of data elements into coherent stories reveals that thematically similar experiences also have a highly personal imprint. Understanding a carer's individual experiences and needs in a contextual, storied manner can reveal information that is crucial to the collaboration of help that is perceived as helpful within a home-based approach to a mental health crisis.